Optimized cesarean techniques, IVF use, and foster strain selection enhance germ-free mouse production efficiency - Yuting Yang; Weimin He; Jingqiang Li; Jinhui Wang; Yuyan Tang; Haitao Shang (Scientific Reports)
Abstract This study aims to refine sterile cesarean section techniques, in vitro fertilization (IVF) and foster mother selection strategies to enhance the efficiency of germ-free (GF) mouse production. We conducted the following analyses: (1) comparing different cesarean section methods, (2) evaluating the impact of natural mating versus in vitro fertilization (IVF) for obtaining donor mice, and (3) assessing maternal care among three inbred strains (C57BL/6J, BALB/c, NSG) and one outbred strain (KM) as GF foster mothers. The results showed that optimizing surgical methods which preserve the female reproductive tract during cesarean section (FRT-CS), significantly improved fetal survival rates while maintaining sterility. IVF enabled precise control over donor delivery dates, enhancing experimental reproducibility. Among GF foster strains, BALB/c and NSG mice exhibited superior nursing and weaning success, whereas C57BL/6J had the lowest weaning rate, in stark contrast to findings on maternal care in SPF C57BL/6J foster mothers. These findings offer practical guidance for optimizing GF mouse production, improving the efficiency of obtaining germ-free mice through cesarean derivation.